1.12 Clinical Problems - COPD 2015
DOI: 10.1183/13993003.congress-2015.pa4798
|View full text |Cite
|
Sign up to set email alerts
|

Six minute walk distance (6MWD) and pulmonary diffusing capacity (DLCO) in patients with COPD

Abstract: Background and Aims: Spirometry is noninvasive test for diagnosis , assessment airflow limitation and to plan management in COPD. GOLD guideline recommended to evaluate staging in airflow obstruction by post-bronchodilator FEV 1 level before treatment. FEV 1 may be correlated with dyspnea symptoms and health status but takes time to evaluate for outpatient visit .The 6-minute walk test (6MWT) is a practical simple test that requires no expensive equipment or advanced training technicians and correlates better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There is another study which compares exercise test with DLCO that showed a significant correlation. 5 It also depicts that exercise capacity worsens as the DLCO value decreases. A study, which we had conducted on patients with COPD also exhibited a significant correlation between the severity of COPD with various categories of DLCO (unpublished).…”
mentioning
confidence: 94%
“…There is another study which compares exercise test with DLCO that showed a significant correlation. 5 It also depicts that exercise capacity worsens as the DLCO value decreases. A study, which we had conducted on patients with COPD also exhibited a significant correlation between the severity of COPD with various categories of DLCO (unpublished).…”
mentioning
confidence: 94%